Recipe development for the kidney patient - AKDUMAN, GÜL (My University, 2021)
Kidney patients are restricted from sodium, potassium, phosphorus, and protein. In thisstudy, new recipes have been developed in order to prevent the decrease in appetite, to control the loss of liquid electrolytes due to vomiting, to help patients feel better by improving their morale, to facilitate their adaptation to the diet. Eight selected foods were prepared by modified for reducing sodium, potassium, and phosphorus (repeating 2 times) and by standard recipes (repeating two times). Eight foods and 16 recipes were obtained. Sodium, potassium, phosphorus, and protein contents were measured after the process. Sodium, potassium, and phosphorus contents were analyzed with the ICP-MS method. Protein content was analyzed with the Kjeldahl nitrogen determination method. Applied cooking methods led to a decrease in sodium, potassium, phosphorus, and protein levels in the modified foods. The highest loss rate (65.3%) was observed in proteins in apple halva. The lowest loss (21.5%) was determined in the potassium in the banana cake. These cooking methods can be useful for enriching the meals of kidney patients.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Urology